Publication trends and hotspots of colorectal adenoma during 2002-2022: a bibliometric and visualized analysis - Li, Xue; Zhang, Wenzheng; Yuan, Surui; Mao, Qiyuan; Zhang, Chuchu; Cai, Ruijuan; Lin, Hongsheng; Wang, Xueqian (Frontiers in Oncology, 2023)
Background: Prevention and treatment of colorectal adenoma (CRA) are great significant to reduce morbidity and mortality of colorectal cancer. Although there have been numerous studies on CRA recently, few publications utilized the bibliometrics to evaluate this field. The objective of current study was to provide a comprehensive analysis of the current state and frontier progress of CRA over the past 20 years. Methods: The Web of Science Core Collection was utilized to extracted all studies of CRA during 2002-2022. Bibliometric tools including CiteSpace, VOSviewer, and the Online Analysis Platform of Literature Metrology were used for statistical analysis. CiteSpace and the Online Analysis Platform were used to evaluate the contributions of various countries/regions, institutions, authors, and journals in this field. Research hotspots and trends were identified through keywords and references analysis by VOSviewer and CiteSpace. Results: 2,268 publications from 2002 to 2022 in total were identified. The number of global publications in this field has increased annually. The USA was the most productive country, contributing nearly 30% of global publications. But in recent years, China’s publications grew rapidly and had the highest citation strength. The most productive institutions was the National Cancer Institute. Baron JA from the USA was the most productive and the one of most co-cited authors. Cancer Epidemiology Biomarkers & Prevention had the highest number of publications and Gastroenterology was the most co-cited journals. Analysis of keywords clusters showed that “mechanism/pathophysiology”, “risk factors and prevention”, “colonoscopy screening and treatment”, “metabolism”, and “microbiota” were the major frontier topics and the main research directions. Conclusions: CRA publications have shown a gradual upward trend in recent years, most of which have been published by developed countries. Developing countries should further focus on CRA research and transnational cooperation with developed countries in the future, in order to better improve the situation of the increasing morbidity and mortality of CRC. Baron JA was the most outstanding researcher in this field. More attention should be devoted to “pathogenesis of CRA”, “less invasive diagnostic methods”, “chemoprevention”, and “screening and risk prediction of CRA including gut microbiome and metabolism”, which will be frontiers in the future.